Single cultures of acinetobacter sp. and cellulosimicrobium sp. grown in pineapple waste: adaption study and potential in reducing COD from real textile wastewater / Nor Habibah Mohd Rosli and Wan Azlina Ahmad - Mohd Rosli, Nor Habibah; Ahmad, Wan Azlina (2018)
Wastewater from industrial plants such as textile, electroplating and petroleum refineries contains various substances that tend to increase the chemical oxygen demand (COD) of the wastewater. Therefore, it is desired to develop a process suitable for treating the wastewater to meet the regulatory limits. This work was conducted to investigate the potential of adapted single culture of A. baumannii, A.calcoaceticus and C.cellulans in reducing COD in real textile wastewater. The study was carried out by adapting each single culture (10% inoculums) to increasing concentration (1%, 2.5 %, 5%, 7.5 % and 10%) of textile wastewater. Then it was introduced to the textile effluent without pH adjustment for five days and the COD values were measured. The textile wastewater was supplemented with pineapple waste for bacterial growth and metabolism. Results obtained showed that pineapple waste was a good nutrient supply for the growth of the bacteria and the best concentration of textile wastewater for adaptation was at 2.5%. The results also showed that A.calcoaceticus shows highest COD reduction with 67% removal whereas A. baumannii and C.cellulans with 60% and 58% removal respectively. The outcome supported that the single culture used in this study showed considerably high reduction of COD from real textile wastewater.